Extracellular Vesicles: A New Paradigm for Cellular Communication in Perioperative Medicine, Critical Care, and Pain Management. (22nd July 2021) - Zhou, Yingqiu K.; Patel, Hemal H.; Roth, David M.
Abstract : Extracellular vesicles (EVs) play critical roles in many health and disease states, including ischemia, inflammation, and pain, which are major concerns in the perioperative period and in critically ill patients. EVs are functionally active, nanometer-sized, membrane-bound vesicles actively secreted by all cells. Cell signaling is essential to physiological and pathological processes, and EVs have recently emerged as key players in intercellular communication. Recent studies in EV biology have improved our mechanistic knowledge of the pathophysiological processes in perioperative and critical care patients. Studies also show promise in using EVs in novel diagnostic and therapeutic clinical applications. This review considers the current advances and gaps in knowledge of EVs in the areas of ischemia, inflammation, pain, and in organ systems that are most relevant to anesthesiology, perioperative medicine, critical care, and pain management. We expect the reader will better understand the relationship between EVs and perioperative and critical care pathophysiological states and their potential use as novel diagnostic and therapeutic modalities.